Genetic Modification of T Cells - Richard A. Morgan (Biomedicines, 2016)
Gene transfer technology and its application to human gene therapy greatly expanded in the last decade. One area of investigation that appears particularly promising is the transfer of new genetic material into T cells for the potential treatment of cancer. Herein, we describe several core technologies that now yield high-efficiency gene transfer into primary human T cells. These gene transfer techniques include viral-based gene transfer methods based on modified Retroviridae and non-viral methods such as DNA-based transposons and direct transfer of mRNA by electroporation. Where specific examples are cited, we emphasize the transfer of chimeric antigen receptors (CARs) to T cells, which permits engineered T cells to recognize potential tumor antigens.